2010
DOI: 10.1111/j.1751-1097.2010.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of the Pharmacological Inhibition of Staphylococcus aureus Multidrug Resistance Pumps and the Variable Levels of the Uptake of the Sensitizer in the Strain‐Dependent Response of Staphylococcus aureus to PPArg2‐Based Photodynamic Inactivation

Abstract: The emergence of antibiotic resistance among pathogenic bacteria has caused an urgent need for the development of alternative therapeutics. One possibility is a combination of nontoxic photosensitizers (PS) and visible light, recognized as photodynamic therapy. Although it is known that Staphylococcus aureus is susceptible to photodynamic inactivation (PDI), the factors that determine the emerging variation among strains in the response to the treatment remain unclear. Some data indicate that cationic photosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…So far only the bactericidal effect of photodynamic inactivation against methicillinresistant and methicillin-susceptible S. aureus is straindependent, which means that different photodynamic parameters (applied radiant exposure, concentration, and incubation time) are necessary to achieve a complete eradication of different pathogens tested [22]. Furthermore, the strain-dependent differences of bactericidal photodynamic inactivation could not be correlated to either the levels of photosensitizer uptake or the pharmacological inhibition of the efflux pump [24]. Therefore, other factors might be influencing such observed differences in the photodynamic efficacy, such as aggregation of the photosensitizer, concentration of antioxidant enzymes, or cellular repair proteins, but all of these factors are not responsible for diminishing TMPyP-induced photosensitization because up to now, there is a lack of selection of photo-resistant bacteria after multiple photodynamic treatments [27].…”
Section: Discussionmentioning
confidence: 91%
“…So far only the bactericidal effect of photodynamic inactivation against methicillinresistant and methicillin-susceptible S. aureus is straindependent, which means that different photodynamic parameters (applied radiant exposure, concentration, and incubation time) are necessary to achieve a complete eradication of different pathogens tested [22]. Furthermore, the strain-dependent differences of bactericidal photodynamic inactivation could not be correlated to either the levels of photosensitizer uptake or the pharmacological inhibition of the efflux pump [24]. Therefore, other factors might be influencing such observed differences in the photodynamic efficacy, such as aggregation of the photosensitizer, concentration of antioxidant enzymes, or cellular repair proteins, but all of these factors are not responsible for diminishing TMPyP-induced photosensitization because up to now, there is a lack of selection of photo-resistant bacteria after multiple photodynamic treatments [27].…”
Section: Discussionmentioning
confidence: 91%
“…10,23,24 Some S. aureus are known for being able to produce biofilms in order to enhance their tenacity in biotic surfaces; therefore, biofilm formation could lead to reduced susceptibility to photoinactivation. To investigate whether MRSA and MSSA strains differ in their ability to form biofilms, we have checked if studied strains are biofilm producers.…”
Section: Discussionmentioning
confidence: 99%
“…5;9 However, our research group has recently described the effect of the strain-dependent response of S. aureus to PDI, and indicated that MRSA strains could be characterized by elevated PDI resistance when compared with methicillin-sensitive S. aureus (MSSA) strains. 10,11 The mechanism underlying this phenomenon is still poorly understood. Therefore, the current study aimed to provide statistically relevant evidence as to whether the response of MRSA strains to PDI differs significantly from that of MSSA, and whether it results from antimicrobial resistance mechanisms or susceptibility to routinely used antimicrobials.…”
mentioning
confidence: 99%
“…us, in vitro studies have concentrated more on bio�lm models as well as in vivo models, particularly rat and mouse models of infected wounds ( Table 2). As we have discussed previously, when studying the use of photoinactivation in bio�lm-related models, the mechanism of strain-dependent response to PDI requires further investigation [50][51][52][53].…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%